PENGGUNAAN MEDIA VIDEO ANIMASI UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MATERI BAGIAN-BAGIAN MATA DAN FUNGSINYA KELAS V-B SDN KANDANGAN I SURABAYA - Lovina Imelda Yunita; Suprayitno; Sri Wahyuningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research uses PTK (Classroom Action Research). Where the model used is Kemis & Deadline. This research focuses on improving student learning outcomes through learning media. The results obtained regarding the effectiveness of the animated video media used experienced quite high significance in each cycle, reaching 63% and 82%. In terms of completeness, students' learning outcomes also increase in each cycle with a percentage gain of 71.88% to 84.37%. So from the results of this research it was concluded that applying animated video media to the material on the parts of the eye and their functions was proven to be effective in improving the learning outcomes of class V students.